Alcohol use among young adolescents in low-income and middle-income countries: a population-based study. (June 2018) - Ma, Chuanwei; Bovet, Pascal; Yang, Lili; Zhao, Min; Liang, Yajun; Xi, Bo
Summary: Background: Alcohol use remains a major public health problem worldwide because of its harmful effects on physical and mental health. Few studies have used a standardised methodology to assess alcohol use among adolescents in low-income and middle-income countries (LMICs). In the present study, we aimed to compare the prevalence of alcohol use, drunkenness episodes, and drin king-related problems among young adolescents in LMICs. Methods: For this population-based study, we used individual data from the Global School-based Student Health Surveys (GSHS) from between 2006 and 2013 in adolescents aged 12–15 years in LMICs. Data were collected using an anonymous self-reported questionnaire. This report is based on four questions assessing alcohol use, drunkenness episodes, alcohol-related drinking problems (ever had a hangover, felt sick, got into trouble with family or friends, missed school, or got into fights, as a result of drinking alcohol), and, in those who reported drinking, how alcohol was purchased. We calculated the overall and regional estimates using a meta-analysis with random-effects. Findings: GSHS data from 57 countries, corresponding to a total of 139 649 young adolescents, were included in this study. The prevalence of the variables varied largely according to country and region. The overall prevalence of having at least one drink during the past 30 days was 25·0% (95% CI 19·3–30·7), and was higher among boys (27·5%, 21·9–33·2) than girls (22·5%, 18·8–26·2), and at age 14–15 years (29·0%, 23·1–34·8) than at age 12–13 years (18·9%, 15·3–22·5). The overall prevalence of having been drunk at least once during the lifetime was 17·9% (13·6–22·1); and was higher among boys (21·3%, 16·8–25·7) than girls (14·5%, 12·1–16·9), and at age 14–15 years (21·5%, 17·0–26·0) than at age 12–13 years (12·2%, 9·5–15·0). The overall prevalence of drinking-related problems was 10·6% (8·9–12·2), and was higher among boys (12·5%, 10·4–14·5) than girls (8·9%, 7·5–10·2), and at age 14–15 years (12·3%, 10·4–14·2) than at age 12–13 years (7·8%, 6·6–9·1). Among those reporting drinking, 27·8% (24·8–30·7) accessed alcohol from their friends, 23·2% (19·5–26·9) got it from family, 19·5% (17·5–21·6) bought it in a store, 9·1% (8·0–10·2) gave someone money to buy some, 2·8% (2·3–3·3) stole it, and 14·4% (12·2–16·5) got it by some other way. Interpretation: Alcohol use, lifetime drunkenness, and alcohol-related problems were frequent among young adolescents in LMICs; however, with differences by country, region, sex, and age group. These findings emphasise the need for interventions to reduce alcohol use targeting young adolescents in LMICs with high prevalence of use and alcohol-related problems. Funding: Shandong University.